Pengaruh Kecerdasan Intelektual dan Kecerdasan Emosional dalam Perspektif Neurosains di Dunia Pendidikan - Permata, Indah; Asbari, Masduki; Ariansyah; Aprilia, Merita (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to determine the importance of intellectual intelligence and the influence of emotional intelligence in the world of education. This study report uses a descriptive qualitative lecture method by listening and taking notes because the source of the information was obtained from one of Gita Wirjawan's YouTube channels, namely about "Intelligence & Happiness in a Neuroscience Perspective'' where the content is that one of the keys to happiness is the ability to control emotions so as not to too often hijacks common sense. But from a neuroscience perspective, the extent of the modern human brain, in essence, is not much different from the brains of its predecessors. Neuroscience in developing intellectual intelligence is very important, because the structure of the nervous system underlies human actions in both cognitive, affective and psychomotor aspects. To make it easier to develop intellectual intelligence and emotional intelligence  through interesting and fun learning.